The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201804673
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Cadmium Bipillared‐Layer Open Frameworks: Synthesis, Structures, Sensing of Nitro Compounds, and Capture of Volatile Iodine

Abstract: Fluorescent Cd metal-organic frameworks (MOFs), [Cd 2 (dicarboxylate) 2 (NI-bpy-44) 2 ]( dicarboxylate = benzene-1,4-dicarboxylate (1,4-bdc, 1), 2-bromobenzene-1,4-dicarboxylate (Br-1,4-bdc, 2), 2-nitrobenzene-1,4-dicarboxylate (NO 2 -1,4-bdc, 3), biphenyl-4,4'-dicarboxylate (bpdc, 4); NI-bpy-44 = N-(pyridin-4-yl)-4-(pyridin-4-yl)-1,8-naphthalimide)),f eaturing non-and twofold interpenetrating pcu-type bipillared-layer open structures with sufficient free voids of 58.4, 51.4, 51.5, and 41.4 %, respectively,h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Naphthalimide (NI) derivatives with a large, planar, π‐conjugated arene core(s) are attractive fluorophores in optoelectronics due to their adjustable photoluminescence properties through substitute modifications [28–30] . Upon immobilization with donating functions, such as pyridine and carboxyl, the highly emissive properties of NI derivatives encourage their use in the construction of luminescent MOFs as potential sensor materials [24, 31–33] . Therefore, we have designed a NI‐based bis‐pyridyl ligand, namely, N ‐(pyridin‐4‐yl)‐4‐(pyridin‐4‐yl)‐1,8‐naphthalimide (NI‐bpy‐44), [24] with remarkable fluorescence as a potential provider of luminescence properties in isoreticular pillared‐layer MOFs of various aromatic dicarboxylic acids (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naphthalimide (NI) derivatives with a large, planar, π‐conjugated arene core(s) are attractive fluorophores in optoelectronics due to their adjustable photoluminescence properties through substitute modifications [28–30] . Upon immobilization with donating functions, such as pyridine and carboxyl, the highly emissive properties of NI derivatives encourage their use in the construction of luminescent MOFs as potential sensor materials [24, 31–33] . Therefore, we have designed a NI‐based bis‐pyridyl ligand, namely, N ‐(pyridin‐4‐yl)‐4‐(pyridin‐4‐yl)‐1,8‐naphthalimide (NI‐bpy‐44), [24] with remarkable fluorescence as a potential provider of luminescence properties in isoreticular pillared‐layer MOFs of various aromatic dicarboxylic acids (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…From a topological point of view, a pillared‐layer MOF is usually composed of 2D metal–carboxylate layered nets and (rigid) linear bis‐pyridyl N‐tethering pillars [19–25] . Hence, the formation of (luminescent) isoreticular pillared‐layer MOFs can be reasonably achieved by applying a dual‐ligand synthetic approach (Scheme 1), [19] which is an alternative and effective approach to generate well‐designed porous frameworks with adjustable pore sizes and tunable structural features by simply adjusting the length of the linear bis‐pyridyl pillars [20–22, 26] or by changing the polycarboxylate moieties [23, 24, 27] . Of particular note, as the length of the bridging ligands is increased, MOFs usually possess network interpenetration, which tends to diminish the porosity [19, 25] .…”
Section: Introductionmentioning
confidence: 99%
“…Among various organic ligands, rigid dicarboxylic acids are extensively utilized to construct intriguing structures because of their strong coordination ability and diverse coordination mode . Among the different kinds of N‐containing linkers, bipyridine and their derivatives are widely employed in the construction of versatile MOFs with promising properties . In addition, it has been reported that some MOFs were constructed from rigid dicarboxylate and functionalized bipyridine by the mixed‐ligand strategy, which have intriguing structures and excellent properties .…”
Section: Introductionmentioning
confidence: 99%
“…Among the different kinds of N‐containing linkers, bipyridine and their derivatives are widely employed in the construction of versatile MOFs with promising properties . In addition, it has been reported that some MOFs were constructed from rigid dicarboxylate and functionalized bipyridine by the mixed‐ligand strategy, which have intriguing structures and excellent properties . 2,5‐Bis(4‐pyridyl)thiazolo[5,4‐ d ]thiazole (Py 2 TTz) with rigid π‐conjugated system has good luminescence property , .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is imperative to detect these nitro compounds. Despite a large number of efforts have been applied to detecting nitro explosives, it is still challenging to detect nitro compounds in practical applications . Therefore, we explored the ability of coordination complex 1 to detect some nitro compounds such as 2, 4, 6‐trinitrophenol (TNP), p‐nitroaniline (PNA), p‐nitrophenol (PNP), p‐nitrotoluene (PNT) and nitrobenzene (NB).…”
Section: Introductionmentioning
confidence: 99%